Multiyear Transmission Expansion Planning using Discrete Evolutionary Particle Swarm Optimization - Manuel Costeira da Rocha (2011)
The objective of Transmission Expansion Planning (TEP) is to minimize the network construction and operational costs while satisfying the requirement of delivering electricity safely and reliably to load centres along the planning horizon. This principle is quite simple, but the complexity of the problem and the impact on society transforms TEP on a challenging issue. The objective of this paper is the introduction of a new discrete approach to solve dynamic TEP, based on an improved discrete version of the evolutionary particle swarm optimization (EPSO) meta-heuristic algorithm. The paper includes sections describing in detail the EPSO enhanced approach, the mathematical formulation of the problem, including the objective function and constraints, and the application of EPSO to this problem. Finally, the use of the developed approach is illustrated using a case study based on the IEEE 24 bus / 38 branch test system.